US Democracy: The Civil Sphere, Public Catholicism, and Alternative Futures - Wood, Richard L. (Concilium, 2026)
Recent decades have witnessed the erosion of the cultural foundations of democracy in the United States, which helped enable the capture of key democratic institutions by anti-civil and anti-democratic forces. This article will briefly diagnose the cultural and institutional erosion that undergirded this crisis of US democracy; sketch the theological commitments through which public Catholicism has opposed and been implicated in democratic erosion; outline four plausible future scenarios that may emerge; and argue that Catholicism will play a key role in determining which of those scenarios actually occurs.